Deformation twinning in the full-α″ martensitic Ti–25Ta–20Nb shape memory alloy. (15th February 2016) - Bertrand, Emmanuel; Castany, Philippe; Yang, Yang; Menou, Edern; Gloriant, Thierry
Abstract: Deformation twinning of the Ti–25Ta–20Nb (mass%) shape memory alloy is characterized using EBSD and TEM. The selfaccommodating α″ microstructure is shown to be first deformed using 111α ″ type I and <211>α ″ type II reorientation twinning. Plastic deformation occurs further by plastic twinning with a new 130<310>α ″ twinning system. Maximum lattice deformation calculation is a relevant parameter to predict the variant of martensite that is favored during the reorientation process. Conversely, Schmid factor analysis can be used to predict the selection of 130<310>α ″ twinning variants during deformation. Analogy between 130<310>α ″ and 332<113>β twinning systems is highlighted. Graphical abstract: